Hydrogen Production from Pure Water via Piezoelectric‐assisted Visible‐light Photocatalysis of CdS Nanorod Arrays. Issue 16 (28th June 2018) - Zhao, Yan; Fang, Zhi‐Bin; Feng, Wenhui; Wang, Kaiqiang; Huang, Xueyan; Liu, Ping
Abstract: Visible‐light‐driven H2 production from pure water is highly promising but unfortunately inefficient. Herein, for the first time, we report the realization of pure‐water‐splitting H2 production under visible‐light irradiation via single‐component CdS without any cocatalysts, employing a piezoelectric‐photocatalysis strategy. Wurtzite CdS nanorod arrays that combine piezoelectric and visible‐light photocatalytic properties was in‐situ assembled on FTO substrates to harvest both solar energy and ultrasonic vibration energy in water. The ultrasound‐induced piezoelectric field in CdS drives the separation of photo‐generated charge carriers, leading to more facile water‐splitting for H2 evolution than that under visible‐light irradiation alone. The CdS nanorod arrays achieves a high H2 production rate of 20 μL . h −1 under optimized coupling field, which is much higher than that of unsupported samples. This work demonstrates the capability of piezoelectric photocatalysts to simultaneously convert visible light energy and acoustic energy into hydrogen energy, which may break a new ground for the design of energy‐conversion materials towards harvesting discrete ambient energy in urban environment. Abstract : Getting down to light and sound : Visible‐light H2 evolution from pure water is realized by CdS photocatalyst with the indispensable assistance of ultrasonic vibration. A new fundamental mechanism of synergetic photo‐sono‐catalysis is proposed and proved, that is, photo‐generated electrons and holes are efficiently separated and reversely enriched on the surface of CdS nanorods by the ultrasound‐induced internal piezoelectric field.